The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11802-008-0385-6
|View full text |Cite
|
Sign up to set email alerts
|

Study on the seasonal variation of the suspended sediment distribution and transportation in the East China Seas based on SeaWiFS data

Abstract: The monthly mean suspended sediment concentration in the upper layer of the East China Seas was derived from the retrieval of the monthly binned SeaWiFS Level 3 data during 1998 to 2006. The seasonal variation and spatial distribution of the suspended sediment concentration in the study area were investigated. It was found that the suspended sediment distribution presents apparent spatial characteristics and seasonal variations, which are mainly affected by the resuspension and transportation of the suspended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 2 publications
1
25
0
Order By: Relevance
“…Duo to the influence of East Asian monsoon, the entire water column produces a strong vertical mixing (Bian et al, 2010;Dong et al, 2011;Li et al, 2010;Shi & Wang, 2010;Wang & Jiang, 2008). Previous researchers reported that the temperature decreases significantly with the depth increasing in the period of late fall to early spring.…”
Section: Discussionmentioning
confidence: 99%
“…Duo to the influence of East Asian monsoon, the entire water column produces a strong vertical mixing (Bian et al, 2010;Dong et al, 2011;Li et al, 2010;Shi & Wang, 2010;Wang & Jiang, 2008). Previous researchers reported that the temperature decreases significantly with the depth increasing in the period of late fall to early spring.…”
Section: Discussionmentioning
confidence: 99%
“…Here, k 0 is the coefficient for clear water, k 1 is the light attenuation due to SPM absorption, C SPM is the satellite derived monthly SPM concentration (Wang and Jiang, 2008), k 2 is the self-shading by chlorophyll a, C CHLa (z) is the profile of simulated chlorophyll a. The values of these parameters are listed in Table 1.…”
Section: Model Configuration and Data Sourcesmentioning
confidence: 99%
“…Furthermore, the two MODIS sensors have collected more than 10 years' worth of data on the Earth's surface, and this image archive provides a great opportunity to monitor and analyze the long-term spatiotemporal dynamics of parameters of the Earth's surface, such as SS [41]. Many studies have shown the potential to detect water components and concentrations in complex waters with MODIS data [39,42,43].…”
Section: Remote Sensing Observationsmentioning
confidence: 99%